Autofluorescence as a noninvasive biomarker of senescence and advanced glycation end products in Caenorhabditis elegans - Tomomi Komura; Mikihiro Yamanaka; Kohji Nishimura; Keita Hara; Yoshikazu Nishikawa (npj Aging and Mechanisms of Disease, 2021)
Abstract To assess the utility of autofluorescence as a noninvasive biomarker of senescence in Caenorhabditis elegans, we measured the autofluorescence of individual nematodes using spectrofluorometry. The fluorescence of each worm increased with age. Animals with lower fluorescence intensity exhibited longer life expectancy. When proteins extracted from worms were incubated with sugars, the fluorescence intensity and the concentration of advanced glycation end products (AGEs) increased over time. Ribose enhanced these changes not only in vitro but also in vivo. The glycation blocker rifampicin suppressed this rise in fluorescence. High-resolution mass spectrometry revealed that vitellogenins accumulated in old worms, and glycated vitellogenins emitted six-fold higher fluorescence than naive vitellogenins. The increase in fluorescence with ageing originates from glycated substances, and therefore could serve as a useful noninvasive biomarker of AGEs. C. elegans can serve as a new model to look for anti-AGE factors and to study the relationship between AGEs and senescence.